2010
DOI: 10.1089/ten.tec.2009.0012
|View full text |Cite
|
Sign up to set email alerts
|

Use of Iodixanol Self-Generated Density Gradients to Enrich for Viable Urothelial Cells from Nonneurogenic and Neurogenic Bladder Tissue

Abstract: Suspensions of viable urothelial cells (UC) isolated from patient bladder biopsies often contain considerable amounts of extraneous materials comprised of cellular debris, dead and dying UC, and red blood cells. We have consistently observed an inversely proportional relationship between UC attachment efficiency and the amount of extraneous materials in the suspension; viable UC cell attachment efficiency decreases as the amount of extraneous materials in the cell suspension increases. Processing the initial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…7,8,27 Four-step density gradients, optimized for each species, separated UNFX cells into five subpopulations, designated B1 to B5. Detailed gene array analysis of rodent cells revealed that the B2 subpopulation was enriched for tubular epithelial cells (see Supplementary Data available online at www.liebertonline.com/ ten).…”
Section: Isolation Of Defined Subpopulations From Established Culturementioning
confidence: 99%
“…7,8,27 Four-step density gradients, optimized for each species, separated UNFX cells into five subpopulations, designated B1 to B5. Detailed gene array analysis of rodent cells revealed that the B2 subpopulation was enriched for tubular epithelial cells (see Supplementary Data available online at www.liebertonline.com/ ten).…”
Section: Isolation Of Defined Subpopulations From Established Culturementioning
confidence: 99%
“…To prevent sedimentation, a density-matching solution, such as OptiPrep (iodixanol) 89 , can be added to the growth medium in order to increase its density so that it matches that of the cells. Proper density matching prevents sedimentation and clumping, enabling encapsulation efficiency of beads and cells to remain nearly constant over periods of up to 2 h, without adverse cytotoxic effects 90,91 . An alternative method for preventing cell sedimentation and aggregation is to place a mini stir bar in the cell suspension syringe 27,92 .…”
Section: Introductionmentioning
confidence: 99%